2018
DOI: 10.1039/c8py00034d
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic synthesis of polypeptides consisting of periodic di- and tri-peptide motifs similar to elastin

Abstract: Elastin-like polypeptides containing proline were synthesized via chemoenzymatic polymerization and exhibited a temperature-dependent structural transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Gross et al synthesized alternating polypeptides via protease-catalyzed polymerization of dipeptide esters, such as AlaGly and LysLeu ethyl esters [18,19]. We also demonstrated that the papaincatalyzed copolymerization of the ValProGly tripeptide and ValGly dipeptide esters afforded poly(ValProGly-co-ValGly), which possesses a periodic sequence similar to that of elastin, a structural protein exhibiting excellent elasticity [20]. The resulting polypeptides showed a reversible structural transition in response to temperature change, which is an essential characteristic for elastin to form a cross-linked hierarchical structure.…”
Section: Introductionmentioning
confidence: 57%
“…Gross et al synthesized alternating polypeptides via protease-catalyzed polymerization of dipeptide esters, such as AlaGly and LysLeu ethyl esters [18,19]. We also demonstrated that the papaincatalyzed copolymerization of the ValProGly tripeptide and ValGly dipeptide esters afforded poly(ValProGly-co-ValGly), which possesses a periodic sequence similar to that of elastin, a structural protein exhibiting excellent elasticity [20]. The resulting polypeptides showed a reversible structural transition in response to temperature change, which is an essential characteristic for elastin to form a cross-linked hierarchical structure.…”
Section: Introductionmentioning
confidence: 57%
“…Synthesis of peptide prepolymers for step-growth polymerization is typically achieved using stepwise amino acid coupling, which is relatively time-consuming and repetitive, or NCA ROP, which requires the use of toxic phosgene derivatives, organic solvents, and stringent reaction conditions to achieve peptides with low dispersity [113,114]. Chemoenzymatic polymerization is considered a "green synthetic method", as reactions can be conducted in aqueous solvents with non-toxic bioderived reagents [115,116]. Moreover, chemoenzymatic polymerization overcomes the problem of epimerization by using enzyme catalysts with high reaction specificity.…”
Section: Chemoenzymatic Synthesis Of Prepolymersmentioning
confidence: 99%
“…Specific amino acid motifs of structural proteins that govern their physical properties were derived from the sequence of structural proteins for this purpose. For example, we synthesized a β-sheet crystalline motif and glycine-rich amorphous motif of spider silk proteins 28 and a repetitive motif of elastin 29 that confers elasticity to polypeptides by chemoenzymatic polymerization. The peptide fragments were further conjugated into multiblock polypeptides, which showed specific secondary structures similar to those of natural proteins.…”
Section: Introductionmentioning
confidence: 99%